Diffused Lattice Vibration and Ultralow Thermal Conductivity in the Binary Ln–Nb–O Oxide System. Issue 24 (26th April 2019) - Yang, Jun; Qian, Xin; Pan, Wei; Yang, Ronggui; Li, Zheng; Han, Yi; Zhao, Meng; Huang, Muzhang; Wan, Chunlei
Abstract: In the pursuit of low thermal conductivity materials for thermal management, one always tries to increase the material entropy by increasing the number of components in the materials to scatter heat‐carrying phonons. However, it also drastically increases the technological complexity to synthesize materials with the target complex composition. Here, a material family is presented with simple composition Ln3 NbO7, which only contains binary oxides of Ln2 O3 (Ln = Dy, Er, Y, Yb) and Nb2 O5 . The thermal conductivities approach the theoretical minimum limit, where the large chemical inhomogeneity due to the charge disorder and fluctuation of bonding length in Ln3 NbO7 plays a major role. Despite the simple composition, Ln3 NbO7 demonstrates an unprecedentedly high scattering rate of vibration states, as confirmed by the highest elastic constant/thermal conductivity ratio, as well as the diffused wavevector‐frequency dispersion. In contrast to the conventional wisdom that low thermal conductivity materials should be explored in the pool of "complex" multiple‐component materials, this work points out an avenue to look into materials with simple composition but large internal chemical inhomogeneity, which would be of both scientific and technological significance in the fields of thermal barrier coating, thermoelectric materials, etc. Abstract : An amorphous‐like thermal conductivity is obtained in the binary Ln–Nb–O oxides, Ln3 NbO7 (Ln = Dy, Y, Er, Yb), which is caused by the lattice disorder and the chemical inhomogeneity. The thermal energy is mainly transported by diffusive wavepackets, i.e., diffusons, for which the wavevector‐frequency dispersion smears out and the polarizations become spatially random.